Bioprosthetic valve fracture: Predictors of outcome and follow‐up. Results from a multicenter study. Issue 4 (15th May 2021) - Brinkmann, Christina; Abdel‐Wahab, Mohamed; Bedogni, Francesco; Bhadra, Oliver D.; Charbonnier, Gaetan; Conradi, Lenard; Hildick‐Smith, David; Kargoli, Faraj; Latib, Azeem; Van Mieghem, Nicolas M.; Miura, Mizuki; Mylotte, Darren; et al.
Abstract: Objectives: To evaluate outcome and its predictors of bioprosthetic valve fracture (BVF) in patients undergoing valve‐in‐valve transcatheter aortic valve replacement (VIV‐TAVR). Background: BVF is feasible and reduces transvalvular gradients in VIV‐TAVR‐procedures, but follow‐up‐data and information on factors influencing the outcome are missing. Methods: The 81 cases of BVF‐VIV‐TAVR were collected from 14 international centers. Results: Predominantly transcatheter heart valve (THV) was implanted first, followed by BVF. VARC‐2 defined device success was 93%, most failures were attributed to residual high gradients. Mean gradients decreased from 37 ± 13 mmHg to 10.8 ± 5.9 mmHg (p < 0.001). BVF reduced the gradient by 16 mmHg. During follow‐up (FU, 281 ± 164 days) mean gradient remained stable (10.8 ± 5.9 mmHg at discharge, 12.4 ± 6.3 mmHg at FU, p = ns). In‐hospital major adverse events occurred in 3.7%. Event‐free survival at 276 ± 237.6 days was 95.4%. The linear mixed model identified balloon‐expandable valves (BEV), Mitroflow surgical valve, stenotic surgical bioprostheses and balloon only 1 mm larger than the true internal diameter of the surgical valve as predictors for higher gradients. Conclusions: BVF is safe and can significantly reduce gradients, which remain stable at FU. BEV, Mitroflow surgical valve, stenotic bioprostheses and balloon larger than the true internal diameter of the surgical valve of only 1 mm are predictors for higher final gradients.